Hakikat Manusia dalam Dunia Pendidikan sebagai Pendidik dan Peserta Didik - Mujia Arrizhma; Mas Ummu Chasbiyah; Muhammad Yusron Maulana El-Yunusi (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
Humans are creatures created by God Almighty who also have reason and thoughts. The fact that humans are equipped with reason, thoughts, feelings and beliefs is a characteristic that distinguishes humans from other creatures. Education and teaching is the process of changing the attitudes and behavior of a person or group of people to mature humans. In other words, education is the process of educating. The aim of the importance of the world of education is to understand the nature of humans in the world of education, both as educators and students, therefore education is used as a means of human nature in the world, both as educators and students. This research uses the library research method, namely the researcher analyzes written literature as the main source. Human nature research in education offers in-depth knowledge to teachers and students. Deeper understanding of the learning process, creating an inclusive learning approach, increasing social interaction in the classroom, empowering students, developing morals and character, and creating a beneficial learning environment are some of the results of this research. This knowledge enables the development of creative and new teaching methods that provide more satisfying and productive learning opportunities for all students.